The Art of Gravity : Poems - Rogoff, Jay (Book collections on Project MUSE., 2011)
George Balanchine, one of the twentieth centuryAEs foremost choreographers, strove to make music visible through dance. In The Art of Gravity, Jay Rogoff extends this alchemy into poetry, discovering in dancing of every kind, from visionary ballets to Lindy-hopping at a drunken party, the secret rhythms of our imaginations and the patterns of our lives. The poems unfold in a rich variety of forms, both traditional and experimental. Some focus on how Edgar DegasAEs paintings expose the artifice and artistic self-consciousness of ballet while, paradoxically, illuminating how it creates rapture. Oth.